2016
DOI: 10.1183/23120541.00049-2015
|View full text |Cite
|
Sign up to set email alerts
|

Sleep clinical record: what differences in school and preschool children?

Abstract: The sleep clinical record (SCR) may be a valid method for detecting children with obstructive sleep apnoea (OSA). This study aimed to evaluate whether there were differences in SCR depending on age and to identify the possible risk factors for OSA development.We enrolled children with sleep disordered breathing between 2013 and 2015, and divided them according to age into preschool- and school-age groups. All patients underwent SCR and polysomnography.OSA was detected in 81.1% and 83.6% of preschool- and schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Brazilian children showed a higher frequency of tonsillar hypertrophy, malocclusion, and alteration of Friedman palate position, whereas Italian children presented with a higher incidence of nasal alterations and arched palate. Previous Italian studies showed an influence of malocclusion, nasal obstruction, and arched palate in the SCR evaluation [10] , [19] . As far as the influence of race in pediatric OSA is concerned, existing literature shows a correlation between the African American race and OSA severity [16] .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Brazilian children showed a higher frequency of tonsillar hypertrophy, malocclusion, and alteration of Friedman palate position, whereas Italian children presented with a higher incidence of nasal alterations and arched palate. Previous Italian studies showed an influence of malocclusion, nasal obstruction, and arched palate in the SCR evaluation [10] , [19] . As far as the influence of race in pediatric OSA is concerned, existing literature shows a correlation between the African American race and OSA severity [16] .…”
Section: Discussionmentioning
confidence: 92%
“…Its validity also applies to children after tonsillectomy, thus showing its wide utility for the follow-up of children affected by obstructive disorders. Nevertheless, the SCR has not been used in a different cultural environment [18] , [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Among the existing questionnaires are the sleep clinical record (SCR), 22 which is quite complete, but complex and time-consuming, 13 the OSA-18, which assesses the impact of obstructive symptoms on quality of life, but as a method diagnosis has low sensitivity and specificity, 23 and the PSQ. The PSQ stands out for having high sensitivity and specificity and for being easy and quick to apply, without the need for a doctor or trained professional.…”
Section: Discussionmentioning
confidence: 99%
“…SCS has been evaluated as a tool for the diagnosis of OSAS in symptomatic school-aged and pre-school children with a sensitivity of 96.5% and 74%, respectively. 37 , 38 Among all the items in SCS, the presence of oral breathing, nasal obstruction, septum nose deviation, tonsillar hypertrophy at grade 3 or 4, Friedman palate position III–IV, and a narrow palate was found to be significantly higher in the OSAS group as compared with the primary snoring group. 37 In practice, the assessment and documentation of these clinical features are needed whether or not the scores are computed for the prediction of diagnosis or for monitoring.…”
Section: Diagnosismentioning
confidence: 97%